Blood and ashes / Matt Hilton. - Hilton, Matt. (New York : HarperCollins, 2013)
The police say Brook Reynolds' death in a car accident was just a tragic accident, but her father knows better, and he wants Joe Hunter to bring her killer to justice. Hunter is skeptical until another attack -- and a threat to Brook's sister -- changes his mind. Soon the entire family is under siege and only Joe can truly protect them. The battle to save Brook's family starts Joe Hunter on a trail of death that leads right to the heart of a racist conspiracy. White supremacists want to hold the government to ransom; and they have got their hands on a dirty bomb to make everyone pay attention. But can Joe stop the plotters before they reduce the free world to ashes.
Keywords: Conspiracies -- Fiction; Racism -- Fiction; Suspense fiction